2022
DOI: 10.17660/actahortic.2022.1333.53
|View full text |Cite
|
Sign up to set email alerts
|

Multi-elemental isotope and analog tracer application to measure nutrient uptake and distribution in Malus × domestica Borkh.

Abstract: Plant nutrient uptake is critical to maintain an optimum balance between vegetative and reproductive growth and fruit quality. Nutrient imbalances, and more specifically the relationship of potassium, magnesium and nitrogen to calcium, can be critical for fruit quality in apple (Malus x domestica Borkh.). In perennial plants, it is difficult to conduct short-term experiments to measure plant uptake and distribution in response to either cultivar or treatment because of substantial preexisting nutrient pools al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…These data are consistent with the findings reported by Sallato et al [46], who found a similar trend in rootstock susceptibility in a 'WA 38' planting in Prosser, WA. Mineral nutrient uptake is influenced by rootstock [67,70], scion [71], and soil quality [72], which lends evidence to the argument proposed by Sallato et al [46] who suggested that GS in 'WA 38' is another calcium-related disorder; differences in rootstock capacity to absorb and distribute mineral nutrients could explain why some plantings appear more susceptible than others. Previous authors have tried to clarify the relationship between nutritional status and the onset of physiological disorders in apple.…”
Section: The Effect Of Rootstock and The Role Of Mineral Nutrition On...mentioning
confidence: 85%
“…These data are consistent with the findings reported by Sallato et al [46], who found a similar trend in rootstock susceptibility in a 'WA 38' planting in Prosser, WA. Mineral nutrient uptake is influenced by rootstock [67,70], scion [71], and soil quality [72], which lends evidence to the argument proposed by Sallato et al [46] who suggested that GS in 'WA 38' is another calcium-related disorder; differences in rootstock capacity to absorb and distribute mineral nutrients could explain why some plantings appear more susceptible than others. Previous authors have tried to clarify the relationship between nutritional status and the onset of physiological disorders in apple.…”
Section: The Effect Of Rootstock and The Role Of Mineral Nutrition On...mentioning
confidence: 85%